Collaborative Learning Based on Artificial Intelligence in Improving Intelligent-TPACK (Technological, Pedagogical, and Content Knowledge) in Teaching Practice - Wijanarko, Tiok; Lestariningrum, Anik; Judijanto, Loso; Asmayani; Windrawan, I Gede; Parwoto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The rapid development of AI technology opens up new opportunities in education, but many teachers in Indonesia still lack understanding of the concept of TPACK and its implementation in the classroom, which has an impact on the low quality of learning. AI-based collaborative learning comes as an innovative solution to help teachers develop Intelligent-TPACK, which is the ability to effectively integrate technology in teaching practices through AI-powered collaboration. This study aims to identify the effect of AI-based collaborative learning on teachers' Intelligent-TPACK (Technological, Pedagogical, and Content Knowledge) in teaching practice. This study uses quantitativemethods with an experimental approach, the research design uses pretest-posttest with experimental groups. The sample used amounted to 100 respondents involving kindergarten teachers in Malang City. Data analysis using paired sample t-Test test. The results show that AI assists teachers in effectively integrating technology in teaching practice, improving technological, pedagogical and content skills. AI-based training programs can be an effective model for improving learning quality. The implications of this study show that AI-based training can effectively improve teachers' ability to integrate technology, improve learning quality, and prepare teachers to face the demands of the digital era.